(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Blake’s pouch cyst is a cystic structure that is the posterior inferior cerebellar velum protruding into the cisterna magna occipitalis communicating with the fourth ventricle without obstructing it.